Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1177/1367493517738123
|View full text |Cite
|
Sign up to set email alerts
|

Stress management for headaches in children and adolescents: A review and practical recommendations for health promotion programs and well-being

Abstract: Stress is considered to be the most common factor reported to trigger headaches in children and adolescents. Although tension-type headache and migraine are the two most common types of headache in children and adolescents, they are often untreated, ignoring their stressful background. We provide a narrative review of the available evidence for health-care professionals involved in stress-related headache management and health promotion programs. An integrative plan is delivered through lifestyle improvement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 67 publications
2
16
1
3
Order By: Relevance
“…Future studies, therefore, should consider whether it is feasible to provide the relaxation interventions at the site of the hospital itself. The results of the present study indicate that as part of an integrative primary headache treatment plan, parents and/or children can choose either one of the investigated techniques, depending on personal preferences and those offered at the hospital, in line with the practical recommendations for stress management in paediatric headaches as recently published [ 3 ]. All three interventions studied appeared to be safe, since no adverse events were reported.…”
Section: Discussionsupporting
confidence: 67%
“…Future studies, therefore, should consider whether it is feasible to provide the relaxation interventions at the site of the hospital itself. The results of the present study indicate that as part of an integrative primary headache treatment plan, parents and/or children can choose either one of the investigated techniques, depending on personal preferences and those offered at the hospital, in line with the practical recommendations for stress management in paediatric headaches as recently published [ 3 ]. All three interventions studied appeared to be safe, since no adverse events were reported.…”
Section: Discussionsupporting
confidence: 67%
“…These tools are basic to develop stress control abilities, reducing anxiety states in high academic demand moments, and strengthening student's self-knowledge. In this line, active exercise, playful-sporting, respiratory or emotional control have shown their effectivity to reduce stress in children [75]. Some studies have indicated that active programs in two basic dimensions of action (curricular and extracurricular), could improve the basic conditions to face daily school demands.…”
Section: Discussionmentioning
confidence: 99%
“…Among the benefits derived from physical activity that stand out most are improvements in bone density, reduction of the risk of suffering chronic illnesses, reduction of anxiety levels, and improvement of social relations [22]. Further, a direct association has been found between regular engagement in physical activity and a reduction of life stress levels in those who participate [23]. When an individual engages in physical activity the production of endorphins increases, cortisol levels decrease, and general mood state improves.…”
Section: Introductionmentioning
confidence: 99%